ЕVALUATION OF HEALTHY LIFESTYLING LEVEL IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Potyazhenko, M.M.; Ischeykin, K.Ye.; Nastroha, T.V.; Sokolyuk, N.L.; Kitura, O.Ye. (World of Medicine and Biology, 2020)
In order to develop a personalized approach in patients with COPD - an individual and effective strategy to implement the recommendations, observance of the principles of healthy lifestyle in the first stage, the study of the main risk factors for the disease, on the basis of which developed for each patient an effective personalized strategy for observing the health of the elderly complex with the implementation of patients with curative respiratory gymnastics by Buteyko and hardening of the body - pouring cold water. The authors of the article prove that the observance by the patients with COPD of recommendations for the regulation of lifestyle, nutrition, systematic performance of therapeutic gymnastics by Buteyko and quenching of the body contribute to the achievement of long remission, improvement of quality of life.
Keywords: healthy lifestyle (HLS); chronic obstructive pulmonary disease (COPD)